If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 2 = 4(2x + 1) + -1x + 7 Reorder the terms: 2 + 12x = 4(2x + 1) + -1x + 7 Reorder the terms: 2 + 12x = 4(1 + 2x) + -1x + 7 2 + 12x = (1 * 4 + 2x * 4) + -1x + 7 2 + 12x = (4 + 8x) + -1x + 7 Reorder the terms: 2 + 12x = 4 + 7 + 8x + -1x Combine like terms: 4 + 7 = 11 2 + 12x = 11 + 8x + -1x Combine like terms: 8x + -1x = 7x 2 + 12x = 11 + 7x Solving 2 + 12x = 11 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 2 + 12x + -7x = 11 + 7x + -7x Combine like terms: 12x + -7x = 5x 2 + 5x = 11 + 7x + -7x Combine like terms: 7x + -7x = 0 2 + 5x = 11 + 0 2 + 5x = 11 Add '-2' to each side of the equation. 2 + -2 + 5x = 11 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 11 + -2 5x = 11 + -2 Combine like terms: 11 + -2 = 9 5x = 9 Divide each side by '5'. x = 1.8 Simplifying x = 1.8
| x/-2=47 | | Y=2/3(9) | | x/15+1/3=7/15 | | 12x-166=5x-5 | | 0.18x-5.8=-8.68 | | x/2=32 | | x/8=33 | | 4x/3-9=5 | | 15x+1/3=7/15 | | x/9=13 | | 7x+4=4x+19 | | 3x-10=149 | | x+-2=9 | | (x-10)(x+8)= | | 6(x-3)=3(4x+2) | | 3x-6=x+3 | | n^2+6n+-16= | | 3x-6=0+3 | | (3x-2)(2y-5)= | | 15x+.333=.466 | | 0=15.72+3.2x | | 28+a/6=9 | | 3/16x9=x | | 235*2.5= | | (x-7)(y-9)= | | 3/16x9 | | 232.74-9.50= | | 45x^4=20x^2 | | 8/15x=1/5 | | (x-5)(y+7)= | | y=6(3.5+1.5y)-11 | | 23*3.5= |